Enhancing Ebony? Common Associations With a cis-Regulatory Haplotype for Drosophila melanogaster Thoracic Pigmentation in a Japanese Population and Australian Populations - Telonis-Scott, Marina; Hoffmann, Ary A. (Frontiers in Physiology, 2018)
The molecular underpinnings of pigmentation diversity in Drosophila have recently emerged as a model for understanding how the evolution of different cis-regulatory variants results in common adaptive phenotypes within species. We compared sequence variation in a 5′ regulatory region harboring a modular enhancer containing a ∼0.7-kb core element contributing to abdominal melanisation in African, and a ∼0.5-kb core element contributing to thoracic pigmentation in D. melanogaster from Japan, to tropical and temperate populations from eastern Australia previously shown to be divergent in thoracic pigmentation and ebony expression. The Australian populations exhibited strong association with the core enhancer polymorphism cluster in complete association with Dark and Light phenotypes from Iriomote, Japan. Moreover, the Iriomote Light and Dark core enhancer haplotypes are common to the Australian populations in the direction predicted by pigmentation phenotype. We also confirmed the Japanese patterns of linkage disequilibrium and association of the tropical inversion In(3R)Payne with the Light enhancer haplotype in the Australian tropical light population. A worldwide survey of the ∼0.5-kb ebony control region SNPs and haplotypes in a subset of the Drosophila Genome Nexus (DGN) populations suggest origins in the sub-Saharan ancestral region surrounding Zambia and subsequent invasion following colonization out of Africa. A previous study demonstrated complex within and between population genetic architecture for abdominal pigmentation which is also correlated with thoracic pigmentation in melanized DGN sub-Saharan populations; however, the ∼0.5-kb ebony control region was not associated and both haplotypes are common even in the most intensely pigmented D. melanogaster from high altitude Ethiopia. In the Australian populations, the strong phenotypic association with the enhancer SNPs and haplotypes that at least partly regulates ebony expression in the Iriomote population, our previous work demonstrating opposing clines for thoracic pigmentation and ebony expression, where the expression cline parallels the In(3R)Payne cline, and the concerted evolution of pigmentation intensity and ebony expression under rapid experimental evolution, all point to a common adaptive evolutionary pathway in distinct populations.